Safety and security review for the process industries application of HAZOP, PHA, what-if and SVA reviews - Nolan, Dennis P. (William Andrew ; Elsevier Science [distributor], 2011)
Drawing on decades of industry experience, well-known safety author and senior Loss Prevention specialist at Saudi Aramco Dennis Nolan has distilled the essential procedures and checklists into this practical guide. As well as guiding the reader through the selection and efficient and complete execution of the alphabet soup of Hazard Analysis and Safety Reviews (HAZOP, PHA, What-IF, SVA, LOPA, Bowtie ...), Nolan shares his personal experience and illustrates otherwise dry procedures with real-world examples. Written from the perspective of the author's extensive experience in loss prevention and safety engineering, this comprehensive manual is intended to provide guidance on all the qualitative hazard analyses conducted for industrial and commercial processes, specifically for Preliminary Hazard Analysis (PHA), What-If, and Hazard and Operability (HAZOP) review teams.-It also demonstrates how the methodology and procedures used for these reviews can be adopted and applied to the Security Vulnerability Analysis (SVA) and Site Security Plan (SSP), requirements under the US Department of Homeland Security's Chemical Facility Anti-Terrorism Standard (CFATS) of 2007. The book's pragmatic approach describes the responsibilities, methods, and documentation required for the performance of such procedures and demonstrates how to conduct them in a timely, effective, objective, and consistent manner as may be prescribed by a company's Process Safety Management (PSM) policy and security requirements. As well as updates throughout to reflect changing practices, the third edition incorporates a new section on cost/benefit analysis and descriptions of new qualitative and quantitative safety reviews such as LOPA (Layer of Protection Analysis) and Bow-Tie (a graphical alternative to HAZOP) and a new chapter to address revalidation of studies/reports after 5 years.-As well as providing invaluable personal insights from his career in the process industries, Dennis Nolan has also added a wealth of new real-world examples, bringing the form-filling to life. And for the first time, the forms and checklists are available for purchasers of the book to download - making this a complete safety review toolkit. Helps you to achieve compliance and avoid disasters: Dennis Nolan combines his extensive personal experience with relevant industry examples to provide the checklists and best-practice guidance needed to negotiate the labyrinth of Hazard Analysis and Safety Review procedures. Keeps your knowledge up-to-date: Coverage of the latest forms of Hazard Analysis and Safety Review, including LOPA and Bowtie Saves time ... and money: Demonstrates how each of the typically required reviews is related, so that information and conclusions used on one may be transferred or adapted for another. Also helps you avoid the fines associated with non-compliance, e.g.-fines of up to $25k per day imposed by the Department of Homeland Security in the USA for non-compliance with the Chemical Facility Anti-Terrorism Standard (CFATS).
Previous edition: 2008.
Keywords: Chemical engineering -- Safety measures.; elektronické knihy; electronic books